Desymmetrization of σ-Symmetric Biphenyl-2,6-diyl Diacetate Derivatives by Lipase-Catalyzed Hydrolysis: Unexpected Effect of C(3′)-Substituent on the Enantiotopic Group Selectivity - Ochiai, Mio; Akisawa, Yuki; Kajiyama, Daichi; Matsumoto, Takashi (Synlett, 2019)
Highly enantioselective desymmetrization of σ-symmetric 3′-substituted 2′,6′-dimethoxybiphenyl-2,6-diyl diacetate derivatives to the corresponding monoacetates was effected by using Rhizopus oryzae lipase (ROL) and porcine pancreatic lipase (PPL), despite the remoteness of the C(3′) substituent from the acetate groups. ROL promoted hydrolysis of the pro-S acetates, irrespective of the type of C(3′) substituent, whereas PPL promoted hydrolysis of the pro-R acetates, and selectivity was only attainable when the C(3′) substituent was a polar group.
Keywords: enantioselective reaction; desymmetrization; axial chirality; biphenyls; lipase